Adult Social Behavior with Familiar Partners Following Neonatal Amygdala or Hippocampus Damage - Moadab, Gilda (Behav Neurosci, 2015)
The social behavior in a cohort of adult animals who received ibotenic acid lesions of the amygdala (4 female, 3 male) or hippocampus (5 female, 3 male) as neonates, and sham-operated controls (4 female, 4 male) was evaluated in their home environments with the familiar opposite-sex monkey (pair-mate) with whom they were housed. Amygdala-lesioned animals spent less time with their familiar partners and engaged in higher frequencies of stress-related behaviors than control animals. Hippocampus-lesioned animals spent significantly more time socially engaging their pair-mates than both control and amygdala-lesioned animals. These results suggest that early damage to the amygdala or hippocampus subtly alter patterns of adult social behavior in a familiar context and stand in sharp contrast to extant studies of early damage to the amygdala or hippocampus and to the more dramatically altered patterns of behavior observed after damage to the adult amygdala.